Hubungan Self-Regulated Learning Dengan Dukungan Teman Sebaya Serata Pengaruhnya Terhadap Prestasi Akademik Pada Mahasiswa Fakultas Kedokteran Universitas Riau - Firdaus Firdaus; Tiara Astri Shafaolivia; Riska Norlaili; Citra Auliya Syafira (Fakultas Kedokteran Universitas Riau, 2021)
Self-regulated learning is a student learning method that is active and independent to achieve academic goals by using cognitive learning, self-motivation and behavioral control. One of the factors that can influence self-regulated learning is peer support. This study aims to assess the correlation between the ability of self-regulated learning and peer support in students of the Faculty of Medicine, University of Riau, and to determine its effect on academic achievement. Respondents in this study were 147 students of class 2019. The research data consisted of the results of the self-regulated learning ability questionnaire and the peer support questionnaire, transcript of the CBT exam results, the GPA transcripts. The Pearson analysis showed that there was a significant correlation between the results of the ability of self-regulated learning and peers support with a p value of 0.00 (<0.05) and a positive correlation of 0.464. The effect of self-regulated learning ability on academic achievement, obtained a p-value of 0.043. There was a significant difference between the results of the CBT with low, medium and high self-regulated learning abilities. There was no difference between the Grade Point Average (GPA) based on the independent learning ability of students of the Faculty of Medicine, University of Riau with a p value of 0.43.